Development of a non-dairy kefir fermented beverage based on plant substrates - Cuba Sosa, Lisbeth Anabel (2025)
In response to the growing interest in non-dairy functional foods, this study aimed to develop a symbiotic beverage based on water kefir fermented with Andean plant-based substrates: black mashua, yacon, and spirulina. An extreme vertices mixture design was applied, maintaining constant levels of 12 % sucrose and 15 % kefir grains, to evaluate eight formulations. The variables analyzed included physicochemical parameters (pH, °Brix, titratable acidity), microbiological indicators (lactic acid bacteria count), and sensory attributes (odor, color, and taste). The results showed a significant decrease in pH (from 6.26 to 2.98) and °Brix (from 15 to 7.0), along with an increase in titratable acidity (up to 1.10 %) and lactic acid bacteria counts exceeding 8 log₁₀ CFU/mL on day 7. Sensory evaluation revealed high acceptability in treatments containing black mashua (odor: 4.6; taste: 4.8). The estimated optimal formulation consisted of 2.4625 % mashua, 2.4625 % yacon, and 0.075 % spirulina, yielding 0.696 % lactic acid, 9.25 °Brix, and a pH of 4.02. In conclusion, the addition of these substrates significantly influenced (p < 0.05) the development of formulations with favorable sensory acceptance and microbiological stability, although there remains room for improvement.